A comparative analysis of the performance of common cropping systems used in the production of maize and selected grain legumes in Cameroon - Raymond N. Nkongho; Neni E. Ibeku; Lawrence M. Ndam; David T. Agbor; Godwin S. Yinda (Scientific African, 2024)
Cropping systems and crop combinations are among vital practices to improve land utilisation with the limited arable land resource. Combinations of maize with legumes are common in Cameroon, but there is a knowledge gap on locality specificity of the best cropping system and maize/legume combination for sustained production. The experiment was conducted at the Faculty of Agriculture and Veterinary Medicine Teaching and Research farm, University of Buea. Different cropping systems and crop combinations were planted in a Randomized Complete Block Design with 13 treatments replicated three times. Data collected for vigour and yield parameters, were analyzed for significance using a two-way ANOVA and treatment means compared using Tukey HSD at 5 % probability, while additional data, were analysed for land equivalent and benefit-cost ratio. The findings reveal no significant differences in the yield of maize under different cropping systems, except for maize-dwarf bean mix cropping system (MDBM), which recorded the lowest yield (3.9 t/ha), with maize soybean intercropping (MSBI), recording the highest yield (5.9 t/ha) for maize. Indeterminate legumes (cowpea and climbing beans) recorded significant results for yield (MCPI = 1.7 t/ha; MCBI = 1.8 t/ha) under intercropping system. Likewise, determinate legumes (dwarf beans and soybeans) also recorded significant results for yield (DB = 2.2 t/ha; SB = 3.5 t/ha) under mono cropping system. Land equivalent ratios for intercropping and mixed cropping systems were highest with MCBI = 1.93 and MCBM = 1.76 and the benefit-cost ratios for intercropping and mixed cropping were >1, with MSBI recording the highest ratio of 3.5, followed by MSBM = 3.3. Intercropping and mixed cropping systems and crop combinations were advantageous over monocropping as they gave better land equivalent and benefit-cost ratio. This study provides meaningful findings in bridging the knowledge gap on locality specificity of the best cropping systems and maize/legume combination, for sustained production, locally and nationally. The contribution to the sustainable development goals (SDG), are multidimensional: The enhancement of food security through improved crop yields (SDG2); the promotion of agricultural practices that mitigate environmental degradation (SDG13) and lastly, advocating for biodiversity conservation through the adoption of sustainable cropping systems (SDG15).